A greener Loess Plateau in the future: moderate warming will expand the potential distribution areas of woody species. (24th February 2023) - Guo, Yanlong; Zhao, Zefang; Yuan, Shiwei; Li, Xin
Abstract: Understanding the effect of future global warming on the distribution and diversity of woody species in the Loess Plateau is critical to the vegetation restoration and rebuilding of this area and yet is highly challenging. In the absence of enough experimental data, projection based on species distribution models is the best option for assessing the future shift in species distribution areas. Here, via a comprehensive habitat suitability model, we present an assessment of potential distribution area change for two plant life forms with a total of 42 key woody species, including 21 tree species and 21 shrub species, on the Loess Plateau under multiple scenarios, and based on this information, we explore the responses of regional potential woody species diversity to future global warming. The results showed that moderate warming will promote the expansion of potential distribution areas for most woody species and generally increase regional species diversity, which will result in a greener Loess Plateau. Our results also show that shrub species are more drought-tolerant and less adversely affected by climate change and thus should be considered a priority in vegetation restoration, especially in the arid area of the northern Loess Plateau. These results are helpful for identifying priority restoration areas, selecting appropriate species for artificial planting, and providing useful information for vegetation restoration and management in the future.